The path forward for sustainability of the pension system in a historical context - J. Mertl; R. Valenčík (Управление)
The long-term sustainability and stability of the pension insurance system can be provided on the basis of a pay-as-you-go system, specifically the NDC variant, which can combine the main type of solidarity (between those who can and want to be gainfully active and those for whom the insured event has occurred) with income solidarity. When reforming the pension system in this manner the opportunity arises to begin gradual changes through fully merit system reform and therefore significantly motivating of extending the period of productivity (putting off retirement) through the upgrade of this system for persons who have reached the retirement age as specified by law.This paper aims to substantiate and explore possible changes in this direction that will not endanger anyone’s entitlements when the reforms are implemented (they have got the form of Pareto improvement), as they derive their funds by extending the time of individual productivity. To this end, the possibility of introducing an extension on top of current system of pay-as-you-go insurance, which could be entered voluntarily by persons who have already reached or are near statutory retirement age, is proposed, and modeled. The extension would operate on the principle that the paid premiums will be transformed into a lifetime annuity. The system would be significantly motivating which for most people means extending life at the fullest, associated with the option to retain beneficial social contacts and gradually relax their gainful activity without experiencing an untoward decrease in income.